(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to know the performance of physics teachers in the light of Mayer’s theory and its relationship to the achievement of their students In order to verify the objective of the research, the following null hypotheses were developed: 1) There is no statistically significant difference at the level (0.05) between the average grades of physics teachers in the light of Mayer’s theory and the hypothetical mean of the questionnaire. 2) There is no statistically significant difference at the level (0.05) between the average grades of physics teachers in the light of Mayer’s theory according to the gender variable (males, females) 3) There is no statistically significant difference at the level (0.05) between the average achievement scores of physics teachers and the hypothetical mean of the test. 4) There is no statistically significant correlation at the level (0.05) between the performance level of physics teachers according to Mayer’s theory and the level of their students’ achievement In order to achieve the objectives and hypotheses of the research, the researcher adopted the descriptive approach, and the research sample amounted to (100) physics teachers who study the applied fifth grade students in the preparatory schools affiliated to the Directorate of Education in Babil Governorate, for all genders, and the questionnaire tool was applied to them. The sample amounted to (500) of the applied fifth grade students who are studying physics by the subject’s teachers. The researchers prepared a questionnaire about the performance of physics teachers in the preparatory stage according to Mayer’s cognitive theory and included three axes of teaching performance (planning - implementation - evaluation) where the paragraphs were distributed on it as it consists Each axis consists of eight paragraphs and each paragraph has five alternatives (always, often, sometimes, rarely, never) and its validity was confirmed by presenting it to the arbitrators, and its stability by the Alpha Cro-Nbach method (80%) and an achievement test of the multiple-choice type consisting of (40) A paragraph with four alternatives for each paragraph, its paragraphs included the six levels of Bloom’s classification and its validity was verified by presenting it to the arbitrators, and finding its stability by the Kew-Dr-Richardson method - 20 as it reached (0.85), and the difficulty and strength coefficient were found. discrimination for each item and the effectiveness of the alternatives to the test items, and the researchers reached the following results: - The performance of physics teachers in the light of Mayer’s theory is acceptable; The researchers attribute the use of some modern methods of teaching, and the use of some physics teachers by teaching aids that increase students’ learning. - The results showed that there was no effect of the gender variable between the level of performance of male and female teachers in the light of Mayer’s theory. - The achievement of fifth grade students was statistically significant; That is, the level of their attainment in physics was at the required level. - There is a statistically significant correlation between the grades of physics teachers according to Mayer’s theory and the grades of their students in the achievement test, due to teachers’ use of modern methods and methods and the use of educational aids that increase their academic achievement.